Access and barriers to measures targeted to prevent malaria in pregnancy in rural Kenya - Gikandi, P; Noor, A; Gitonga, C; Ajanga, A; Snow, R (Blackwell Publishing Ltd., 2008)
Objectives: To evaluate barriers preventing pregnant women from using insecticide-treated nets (ITN) and intermittent presumptive treatment (IPT) with sulphadoxine-pyrimethamine (SP) 5 years after the launch of the national malaria strategy promoting these measures in Kenya. Methods: All women aged 15-49 years were interviewed during a community survey in four districts between December 2006 and January 2007. Women pregnant in the last 12 months were asked about their age, parity, education, use of nets, ITN, antenatal care (ANC) services and sulphadoxine-pyrimethamine (SP) (overall and for IPT) during pregnancy. Homestead assets were recorded and used to develop a wealth index. Travel time to ANC clinics was computed using a geographic information system algorithm. Predictors of net and IPT use were defined using multivariate logistic regression. Results: Overall 68% of pregnant women used a net; 52% used an ITN; 84% attended an ANC clinic at least once and 74% at least twice. Fifty-three percent of women took at least one dose of IPT-SP, however only 22% took two or more doses. Women from the least poor homesteads (OR =2.53, 1.36-4.68) and those who used IPT services (OR =1.73, 1.24-2.42) were more likely to sleep under any net. Women who used IPT were more likely to use ITNs (OR = 1.35, 1.03-1.77), while those who lived more than an hour from an ANC clinic were less likely (OR = 0.61, 0.46-0.81) to use ITN. Women with formal education (1.47, 1.01-2.17) and those who used ITN (OR = 1.68, 1.20-2.36) were more likely to have received at least one dose of IPT-SP. Conclusion: Although the use of ITN had increased 10-fold and the use of IPT fourfold since last measured in 2001, coverage remains low. Provider practices in the delivery of protective measures against malaria must change, supported by community awareness campaigns on the importance of mothers' use of IPT.